Theoretical investigation on $$\hbox {BeN}_{{2}}$$ BeN 2 monolayer for an efficient bifunctional water splitting catalyst - M. R. Ashwin Kishore (Nature Portfolio, 2020)
Abstract The search for an active, stable, and abundant semiconductor-based bifunctional catalysts for solar hydrogen production will make a substantial impact on the sustainable development of the society that does not rely on fossil reserves. The photocatalytic water splitting mechanism on a $$\hbox {BeN}_{{2}}$$ BeN 2 monolayer has here been investigated by using state-of-the-art density functional theory calculations. For all possible reaction intermediates, the calculated changes in Gibbs free energy showed that the oxygen evolution reaction will occur at, and above, the potential of 2.06 V (against the NHE) as all elementary steps are exergonic. In the case of the hydrogen evolution reaction, a potential of 0.52 V, or above, was required to make the reaction take place spontaneously. Interestingly, the calculated valence band edge and conduction band edge positions for a $$\hbox {BeN}_{{2}}$$ BeN 2 monolayer are located at the potential of 2.60 V and 0.56 V, respectively. This indicates that the photo-generated holes in the valence band can oxidize water to oxygen, and the photo-generated electrons in the conduction band can spontaneously reduce water to hydrogen. Hence, the results from the present theoretical investigation show that the $$\hbox {BeN}_{{2}}$$ BeN 2 monolayer is an efficient bifunctional water-splitting catalyst, without the need for any co-catalyst.